1974
DOI: 10.1159/000214069
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Susceptibility to Thrombin and Collagen Platelet Aggregation in Man Fed a Low Fat Diet

Abstract: A study was conducted in seven males and eight females to determine the effect of feeding 25 and 35% fat calories on plasma lipids, blood clotting parameters and platelet aggregation. A statistically significant reduction in thrombin- and collagen-induced aggregation was observed at the end of the 25 %-fat-calorie period. At the end of the 35 %-fat-calorie period the thrombin- and collagen-induced aggregation tests rebounded to the predietary level. Platelet counts rose significantly and white blood cell count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…In man, although it has been shown that drastic changes in the diet might modify platelet functions (Iacono 1975, O'Brien et al 1976) over a short period of time, it is practically unknown whether populations differing in their intake of saturated fats (and probably also differing in their susceptibility to coronary heart disease) present differences in their platelet functions.…”
Section: Introductionmentioning
confidence: 99%
“…In man, although it has been shown that drastic changes in the diet might modify platelet functions (Iacono 1975, O'Brien et al 1976) over a short period of time, it is practically unknown whether populations differing in their intake of saturated fats (and probably also differing in their susceptibility to coronary heart disease) present differences in their platelet functions.…”
Section: Introductionmentioning
confidence: 99%
“…With this therapeutic dosage, we observed an increase in GLA and DGLA in erythrocyte membrane phospholipids and an increase in the DGLA/AA ratio but no effect on platelet aggregation and the in vivo 11 dehydrothromboxane B2 level. It is possible that the observed increase in platelet aggregation in Barre's study is not related to the intake of specific components (GLA) of borage oil at all but is related to a substantial additional fat intake (24 g/day), as Iacono et al(1974) reported that feeding high fat calories increased collagen and thrombin induced platelet aggregation.…”
mentioning
confidence: 81%
“…They were healthy male farmers (owners of a farm) born in the same region between January 1st, 1932 and December 31,1937, and also having spent most of their life in the region.…”
Section: Human Studiesmentioning
confidence: 99%